2017
DOI: 10.1177/1534735417736861
|View full text |Cite
|
Sign up to set email alerts
|

A Preclinical Evaluation of the Antitumor Activities of Edible and Medicinal Mushrooms: A Molecular Insight

Abstract: Cancer is the leading cause of morbidity and mortality around the globe. For certain types of cancer, chemotherapy drugs have been extensively used for treatment. However, severe side effects and the development of resistance are the drawbacks of these agents. Therefore, development of new agents with no or minimal side effects is of utmost importance. In this regard, natural compounds are well recognized as drugs in several human ailments, including cancer. One class of fungi, “mushrooms,” contains numerous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 73 publications
1
27
0
Order By: Relevance
“…Mushrooms are widely consumed due to its health-promoting properties. Several lines of evidence depicted the clinical significance of mushroom polysaccharides [ 71 , 72 , 73 , 74 ] including the polysaccharides isolated from the mushroom Dictyophora indusiata [ 50 , 51 , 52 , 53 ]; however, the impact of polysaccharides from mushrooms in general and from D. indusiata in particular on gut microbial ecology has been rarely investigated. In this study, our data revealed that the DIP supplementation restored the gut microbiota community structure, enhanced microbial diversity, reduced the intestinal inflammation, and ameliorated the gut barrier integrity caused by antibiotic administration.…”
Section: Discussionmentioning
confidence: 99%
“…Mushrooms are widely consumed due to its health-promoting properties. Several lines of evidence depicted the clinical significance of mushroom polysaccharides [ 71 , 72 , 73 , 74 ] including the polysaccharides isolated from the mushroom Dictyophora indusiata [ 50 , 51 , 52 , 53 ]; however, the impact of polysaccharides from mushrooms in general and from D. indusiata in particular on gut microbial ecology has been rarely investigated. In this study, our data revealed that the DIP supplementation restored the gut microbiota community structure, enhanced microbial diversity, reduced the intestinal inflammation, and ameliorated the gut barrier integrity caused by antibiotic administration.…”
Section: Discussionmentioning
confidence: 99%
“…A natural treatment for a disease is always the best choice due to its minimum side effects, easy availability and low cost. Among natural products, mushrooms have a long history to be used as a source of food and medicine [ 11 ]. One of the most cultivated mushrooms is Lentinula edodes , which is associated with a number of medicinal properties ranging from anti-microbial to anti-metastatic and anti-cancer to immunomodulation [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This activation of NF-κB results in the transcription of genes that are involved in antiapoptotic ( Survivin , Bcl-xL , Bcl-2 , cIAPs , c-FLIP ) proliferative ( Cyclin-D1 , myc ), proinflammatory ( iNOS , COX-2 ), invasive ( MMP-9 ), and angiogenic ( VGEF ) activities [ 59 , 63 , 64 , 65 ]. Highlighting the fact that the agents that prevent the inactivation of NF-κB may serve as a potential arsenal for combating cancer, several lines of evidence have shown that the mushroom-originated compounds exhibits their anticancer effect by modulating different nodes of signal transduction pathways, including NF-κB [ 66 ]. Herein, our data indicated that Lp16-PSP from L. edodes strain C 91-3 has resulted in the inhibition of NF-κB translocation into the nucleus by reducing the phospho-IκB-α levels ( Figure 2 G).…”
Section: Discussionmentioning
confidence: 99%